Optimization of Production Flow through the CRAFT Method - Modrovský, Radek (Manufacturing Technology Journal, 2019)
The article describes usage of the CRAFT method and its influence on the optimization of flow logistics. The method helps to reduce the cost of basic material flow determination in production, assembly of production units, material handling, storage of individual parts and the transport of finished products. By using the method, long traffic routes, unproductive times and warehouse inventory that unnecessarily increase our costs were removed. In today's competitive environment, it is necessary to improve continuously all processes not only in production, and this method enables us to effectively achieve defined business goals.
Keywords: CRAFT; logistics; production; optimalization; manipulation